“Estimación del índice de mérito total del programa de mejoramiento genético sostenible de bovinos de leche de la parroquia Juan Montalvo”. - Molina Gallardo, Luis Armando (2024)
The main objective of this research project was to estimate the total merit index of the sustainable genetic improvement program for dairy cattle in the Juan Montalvo parish of the Latacunga canton, according to economically important traits. Therefore, for the research we worked with 90 animals and 12 producers who are part of the project. The data collected revealed that the average monthly production cost per liter of milk is $0.45, while the average monthly profit in the Juan Montalvo parish is $735.80, not including labor costs. This analysis raises a concern about the reliability of the records, as many producers are not in the habit of keeping detailed records of their production costs. That is to say, this could lead to an underestimation of actual costs and thus a lack of confidence in making decisions based on this data. The largest expense generated is for feed and medications, with a monthly average of $83.8. The response to selection for daily weight gain averaged 136.45 g/day, to achieve the estimated value (500-700 g/day) is expected to have a positive impact in the third generation; in milk production the average is 3578 kg/lactation, to obtain the estimated value (5000 kg/lactation) 5 generations are needed and for milk density the average was 0.87 g/ml to reach the estimated value (1,032 g/ml) 4 generations are needed. As a matter of fact, these data help a significant contribution for producers for more profitable and sustainable milk production. Then, using the data collected from dairy production, the overall merit index of the genetic improvement program in the Juan Montalvo parish was calculated. In addition, this index identified the best breeding stock in terms of the traits evaluated, including daily weight gain for the Holstein Sacarias, milk production for the Pizan, and milk density for the Holstein Cristina. Undoubtedly, all these traits were selected based on their positive response to selection, thus contributing to the genetic improvement of the dairy population in the region.